Pengaruh Beban Klaim Dan Hasil Underwriting Terhadap Laba Pada Perusahaan Asuransi Jiwa Syariah - Wildaningsih Wildaningsih; Rohma Septiawati; Meliana Puspitasari (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2024)
This study was conducted to examine the effect of claim expenses and underwriting results on the profits of sharia life insurance companies in Indonesia registered with Financial Services Authority during the 2017-2021 period. This research uses quantitative method with multiple linear regression analysis techniques and data processing by SPSS program version 26. It uses secondary data collected from published and audited annual financial statements. Data sample collection using purposive sampling and there were 7 selected companies. The results showed that claim expenses had a negative effect and significant on profits, then underwriting results have a positif effect and insignificant on profit, and the two variables such as claim expenses and underwriting results simultaneously have affect and significantly on profits.